2022
DOI: 10.32604/biocell.2022.015409
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box protein O1 (FoxO1) regulates lipids metabolism and cell proliferation mediated by insulin and PI3K-Akt-mTOR pathway in goose primary hepatocytes

Abstract: In order to explore the role of forkhead box protein O1 (FoxO1) in the lipid metabolism and cell proliferation, goose primary hepatocytes were isolated and incubated with insulin or PI3K-Akt-mTOR pathway dual inhibitor NVP-BEZ235, and then transfected with FoxO1 interference plasmid. The related parameters of lipid metabolism and cell proliferation were measured. The results firstly showed that FoxO1 interference increased the intracellular TG and lipids concentration (P < 0.05); and increased the proliferativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Fork head transcription factor 1(FoxO1), a major target of Akt, is a transcription factor negatively regulated by insulin signaling. Our previous researches had confirmed that PI3K/Akt/mTOR pathway regulated cell proliferation and lipid metabolism via mediating insulin signaling pathway and FoxO1 in goose primary hepatocytes ( Han et al, 2015 ; Han et al, 2016 ; Liu et al, 2016a ; Wei et al, 2022b ). Akt directly inhibited FoxO1 and reduced glucose levels in serum ( Yang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Fork head transcription factor 1(FoxO1), a major target of Akt, is a transcription factor negatively regulated by insulin signaling. Our previous researches had confirmed that PI3K/Akt/mTOR pathway regulated cell proliferation and lipid metabolism via mediating insulin signaling pathway and FoxO1 in goose primary hepatocytes ( Han et al, 2015 ; Han et al, 2016 ; Liu et al, 2016a ; Wei et al, 2022b ). Akt directly inhibited FoxO1 and reduced glucose levels in serum ( Yang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 87%
“…It is generally considered that the formation of fatty liver in goose is primarily due to the imbalance between lipids synthesis, transport and fatty acids β -oxidation in the liver, which leads to excessive lipids deposition in the liver and promotes hepatocytes proliferation. This process is closely associated with endoplasmic reticulum stress, insulin resistance ( IR ) as well as hepatocyte growth and proliferation ( Geng et al, 2015 ; Geng et al, 2016b ; Wei et al, 2022b ). A recent study suggests that the large amount of fat stored in goose liver results from an imbalance between the storage and secretion of exogenous and de novo synthesized endogenous lipids, as well as an absence of leptin gene homologs due to positive selection ( Lu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%